A study on the management system in the healthcare sector using service quality concept - Ahmad, Othman; Ibrahim, Daing Nasir; Noor Azlinna, Azizan; Mustafa, Shariman; Hassan, Hasahudin; Majjah Mazita, Mokhtar; Azit, Azizan; Ghani, Airin Abdul; Ida Rizyani, Tahir; Syamimi Errymy, Sawal (2012)
This study was carried out to investigate the factors that effect to service quality in the healthcare sector and to analyze the relationship between the factors of quality service that influences the customer's satisfaction in healthcare sector. This study carried out on hospitals that are selected in Malaysia including government hospitals and private hospitals. A total of 1000 sets of questionnaires were distributed at 20 hospitals that was selected including government hospitals and private hospitals in the following state Terengganu, Pahang, Negeri Sembilan, Perak, Kedah, Federal Territory, Selangor, Johor and Kelantan. For this research, it uses normality test method, descriptive statistics, and reliability test. Besides that this research analysis use analysis factor and also correlation Pearson test to get the relationship. The data was analyzed using SPSS (Statistical Package For Social Science Version 16.0). For the overall, infrastructure, personnel quality, process of clinical care, administrative procedure, safety measures, corporate image, social responsibility and trustworthiness of the hospitals really gives effect on customer satisfaction and also there have strong relationship between factors in influencing customer's satisfaction.